2004
DOI: 10.1113/jphysiol.2004.068320
|View full text |Cite
|
Sign up to set email alerts
|

Glycine protects cardiomyocytes against lethal reoxygenation injury by inhibiting mitochondrial permeability transition

Abstract: Post-ischaemic reperfusion may precipitate cardiomyocyte death upon correction of intracellular acidosis due in part to mitochondrial permeability transition. We investigated whether glycine, an amino acid with poorly understood cytoprotective properties, may interfere with this mechanism. In cardiomyocyte cultures, addition of glycine during re-energization following 1 h of simulated ischaemia (NaCN/2-deoxyglucose, pH 6.4) completely prevented necrotic cell death associated with pH normalization. Glycine also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
4
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 32 publications
5
52
4
3
Order By: Relevance
“…In relation to this, it is worth mentioning here the recently described increase in apparent detection of Gly by HRMAS with increased recording time in GBM biopsies (48), which was also interpreted by the authors as suggesting higher gly visibility in GBM ex vivo with respect to the in the in vivo tumour MRS pattern. The concentration of gly that displays a protective effect in the various cell systems mentioned above is in the 3-5 mM range (51)(52)(53). This value is very close to the gly content found by us in GBM (3.28 µmol/gtw, Table V).…”
Section: Comparison Of Mi/gly Calculated From In Vivo Data and Mi/glysupporting
confidence: 71%
“…In relation to this, it is worth mentioning here the recently described increase in apparent detection of Gly by HRMAS with increased recording time in GBM biopsies (48), which was also interpreted by the authors as suggesting higher gly visibility in GBM ex vivo with respect to the in the in vivo tumour MRS pattern. The concentration of gly that displays a protective effect in the various cell systems mentioned above is in the 3-5 mM range (51)(52)(53). This value is very close to the gly content found by us in GBM (3.28 µmol/gtw, Table V).…”
Section: Comparison Of Mi/gly Calculated From In Vivo Data and Mi/glysupporting
confidence: 71%
“…However, in marked contrast to the findings in whole perfused hearts, neither apoptotic nor necrotic cell death of HL-1 cells under these conditions was attenuated by 15 min acidic reperfusion. This is in apparent contradiction to one earlier study in HL-1 cells, in which a brief acidic treatment was found to exert significant protection against I/R damage [45]. Notably, however, where we employed true hypoxia in combination with physiologically relevant CO 2 /HCO 3 -buffering, this study [45] employed a "simulated ischemia" protocol in which glucose-and mitochondrial metabolism is poisoned by cyanide and 2-deoxyglucose (2-DOG) to completely block both.…”
Section: Discussioncontrasting
confidence: 53%
“…The HL-1 cells were exposed to 5 h of simulated ischemia (0.5% O 2 , 5% CO 2 , HCO 3 -buffering to pH 6.0, increased K + , and no glucose), followed by 120 min reperfusion, of which the first 15 min was either at pH 7.4 or pH 6.0, and in the absence or presence of EIPA. HL-1 cells undergoing ischemia followed by 120 min neutral reperfusion exhibited a marked increase in both necrotic and apoptotic cell death compared to normoxic controls, consistent with previous reports by us and others [3,18,45]. However, in marked contrast to the findings in whole perfused hearts, neither apoptotic nor necrotic cell death of HL-1 cells under these conditions was attenuated by 15 min acidic reperfusion.…”
Section: Discussioncontrasting
confidence: 51%
“…The results demonstrated that GLY receptor α 1 and β subunitimmunoreactive spots were found not only on the membrane but also in the cytoplasm of cardiomyocytes; this finding is different from that in neurons. Recently, Ruiz-Meana et al found that intracellular glycine exerted an inhibitory effect on mitochondrial permeability transition in cardiomyocytes and that intracellular glycine depletion made the cells more vulnerable to necrotic death during myocardial hypoxia/ reoxygenation [24] . These findings suggest that GLY can act directly on the mitochondria of cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%